Listening styles of ESL instructional leaders in secondary schools in Sri Aman, Sarawak / Garcia Elsie Harris - Harris, Garcia Elsie (2013)
Instructional leaders create the opportunity to develop relationships based on listening. The most obvious problem is, of all the communication skills, listening is the earliest learned and the most frequently used, yet it seems to be the least mastered. Henceforth, this case study was conducted with the aim to identify the listening styles of ESL instructional leaders in secondary schools located in Sri Aman District, Sarawak. The descriptive study comprised 70 ESL teachers from six secondary schools in Sri Aman District, Sarawak. The case study employed a mixed method research design where data were collected via a questionnaire survey and in-depth semistructured interviews. The quantitative data were analysed using SPSS version 17 for Windows while qualitative data were analysed based on the research questions in order to trace emerging patterns. The findings revealed that People-Oriented listening style was the most preferred listening style among ESL instructional leaders followed by Content-Oriented listening style, Time-Oriented listening style and Action-Oriented listening style. Findings also indicated that there were no significant differences in listening styles between male and female ESL instructional leaders. The analysis also depicted that there was no significant difference in listening styles between the novice and experienced ESL instructional leaders. Moreover, findings revealed that there was no significant difference in listening styles between the urban and the rural ESL instructional leaders. Physical distractions, communication style, personal emotion and attitude and non-verbal cues were some of the main challenges faced by ESL instructional leaders. The findings imply that educational leaders need to be attentive of effective listening styles as it can enhance the teaching and learning process. It also may enhance their communication skill in schools.